THE NORMAL RADIOGRAPHIC ANATOMY OF THE FORELIMB IN SUNDA PORCUPINE - Suparmin, Yuliani; Gunanti, Gunanti; Noviana, Deni; Agungpriyono, Srihadi (Buletin Veteriner Udayana, 2019)
The aim of this project is to develop a detailed accessible set of reference images of the normal forelimb radiographic anatomy in sunda porcupine ( Hystrix javanica ), including digit,carpus, metacarpal, radius, ulna, and humerus. This project that using 2 healthy sunda porcupines (male and female) was radiograped using digital radiography and standars projection. Four images, illustrating the normal radiographic anatomy of the forelimb were selected and presented along with detailed description. These image are aimed to be of assistence to veterinary surgeons, veterinary students, medic concervation especially in domestic wild animal, and veterinary researchers by enabling understand of the normal radiographic anatomy of the forelimb, and allowing comparison with the abnormal radiographic.